Analysis of time-out use in female water polo - Ruiz-Lara, E.; Borges-Hernández, P. J.; Ruiz-Barquin, R.; Argudo Iturriaga, F. M. (Journal of Human Sport & Exercise, 2018)
The study seeks to examine the use of time-out in water polo. For this, was analyzed it uses by coaches women's category in Water polo World Championship held in Melbourne, Australia 2007. All matches were recorded by a digital video camera, located in a central and elevated position on the halfway line. Subsequently, several observers unrelated to this study, which had been previously trained, analyzed all downtime analysis using the software Polo Análisis Banquillo v1.0. The variables observed were the quarter of play, the momentary results, the reason to apply, under front and rear situational, the immediate effect and the final score. It is observed that women's water polo coaches make more use of time-out in the last period, with an adverse score, after a temporary expulsion, being equal to pass to inequality, no goal is achieved and its requested further by the losing team.